Lição de coisas: Igreja Católica e formação cultural para o cinema no Brasil e na Bahia - Santos, Raquel Costa (2009)
This paper analyses the Catholic Church influence in the cultural formation for the cinema in Brazil and in Bahia, until the 60s. In spite of many studies gave relevance on Church´s performance as cinema censor device, the development of this analysis is from the role of the Church in social practices configuration of cinema, which is based on historic project of use of image. The theoretical-methodology route is anchored in memory which is considered as a category, object of knowledge and a fact in the world. From the relation between memory and cinema it s possible to understand how are is the union among habitus, practices and trajectories in happenings that ally systems of individual provisions to social conditions of existing, in a movement that organizes the past in a relation with the present. The theoretical assumptions are joined with the quantitative research which is based on bibliography that refers to the topic, historic documents of Catholic Church, newspapers, magazines and interviews. In order to find the way that the religious institute gathered the image as a symbolic element for spirit education , this study begins from the utilization of sacramental arts, optical invents like the dark chamber and the magic lantern, until it reaches the cinema. The latter was seen, at first, as a profane competitor, but soon it was renumbered as a moral and educational instrument and its use required the implementation of international documents and organizations. Speaking of Brazil and Bahia contexts, this paper shows how the catholic hierarchy and the lay apostolate acted in the realization of institutional practices and trajectories of people and groups related to the formation for the cinema and by the cinema